Study on fetomaternal outcome in antepartum haemorrhage - Nathwani, Naimish D.; Vyas, Rupa C.; Shah, Sapana R.; Parikh, Purvi M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Any bleeding from or into the genital tract after the period of viability, but before the birth of the baby is termed as antepartum haemorrhage (APH). Methods: 110 cases of bleeding per vaginal (pv) after 28 weeks of gestation were studied retrospectively from August 2018 to June 2019 and were grouped as placenta previa, placental abruption and indeterminate. Results: 35.45% cases were of placenta previa, 53.63% cases were of placental abruption and 10.90% cases were of indeterminate. Majority were delivered by lower segment caesarean section (LSCS) and most of the cases required blood transfusion. Conclusions: APH cannot reliably be predicted .It is major cause of maternal and perinatal mortality and morbidity. Multidisciplinary approach and senior input is necessary in making decision about timing and mode of delivery. Presently increase in use of ultrasonography (USG) for placental localisation and to diagnose abruption, improved obstetrical and anesthetic facilities, increase in use in blood products to correct anemia and advanced neonatal care facilities, all of these have played important role in decreasing perinatal as well as maternal mortality and morbidity